EFL Teachers’ Preference Teaching Styles: An Interpretative Study - Diah Safithri Armin (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2023)
Teaching style refers to teacher-student interaction, teachers' quality and behavior, classroom management, teaching media, planning subject matter, and teacher's action that affect the effectiveness of the teaching-learning process. Since there is still little research discussing EFL teaching styles in higher education, this study aims to find the EFL teachers' preferred teaching styles in one of Indonesia's universities. This study implemented a basic interpretative study with four EFL teachers as participants who have different teaching experiences. The study results showed that the participants act six out of ten teaching styles provided in the research instrument. Then, the participants prefer the facilitator style in their daily teaching activities. In brief, the participants did some teaching styles, but most of the time, the facilitator style was their typical teaching style.